2013
DOI: 10.1103/physrevb.88.184404
|View full text |Cite
|
Sign up to set email alerts
|

Spin-wave propagation in the presence of interfacial Dzyaloshinskii-Moriya interaction

Abstract: In ferromagnetic thin films, broken inversion symmetry and spin-orbit coupling give rise to interfacial Dzyaloshinskii-Moriya interactions. Analytic expressions for spin-wave properties show that the interfacial Dzyaloshinskii-Moriya interaction leads to non-reciprocal spin-wave propagation, i.e. different properties for spin waves propagating in opposite directions. In favorable situations, it can increase the spin-wave attenuation length. Comparing measured spin wave properties in ferromagnet|normal metal bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
219
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(233 citation statements)
references
References 55 publications
(64 reference statements)
10
219
1
1
Order By: Relevance
“…(28) [Eq. (29)]. The generated DM fieldlike torque (FLT) ∝ m × y and DM dampinglike torque (DLT) ∝ m × (y × m) are in complete analogy with the Rashba torque [8,9].…”
Section: B Magnetization Deviations Induced By the Spin Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…(28) [Eq. (29)]. The generated DM fieldlike torque (FLT) ∝ m × y and DM dampinglike torque (DLT) ∝ m × (y × m) are in complete analogy with the Rashba torque [8,9].…”
Section: B Magnetization Deviations Induced By the Spin Wavesmentioning
confidence: 99%
“…Recently, it has been realized that DMI impacts the propagation of spin waves just like spin-orbit coupling affects the electron flow, resulting in topological behaviors such as the magnon Hall effect and edge currents [27]. It was reported that the DMI effect on the spin-wave dispersion is similar to the Rashba spin-orbit coupling effect on electron dispersion [28][29][30]. Therefore, one anticipates that the spin-orbit torque due to electron flow in Rashba spin-orbit coupled systems might have its counterpart due to magnon flow in systems displaying DMI.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable thought and effort has been brought to bear on exploiting systems with novel anisotropic spinspin interactions (e.g. Dzyaloshinskii-Moriya interactions) [4][5][6][7][8][9][10] and on engineering new structures (e.g. magnonic crystals) for use in tailoring the propagation characteristics of spin waves [11][12][13][14][15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…These methods include both determination of the critical ferromagnetic layer thickness at the transition from a Néel to a Bloch wall 14 , and measurements of domain wall motion 19,20,21 . Furthermore, quantitative experimental comparison of the symmetric and anti--symmetric exchange is still outstanding.Recent theory predicts an asymmetric dispersion shift of long--wavelength thermal spin--waves in magnetic thin films due to the DMI 22,23 . Motivated by this theory, we used Brillouin light scattering (BLS) to directly measure the predicted asymmetric dispersion shift, which in turn allowed us to determine the magnitude and direction of the DMI vector in a technological relevant sample system: we used a series of sputtered multilayer stacks consisting of SiN/Ni 80 Fe 20 (t)/Pt(6 nm)/Ta(3 nm)/substrate where t ranged from 1 nm to 13 nm.…”
mentioning
confidence: 99%
“…Recent theory predicts an asymmetric dispersion shift of long--wavelength thermal spin--waves in magnetic thin films due to the DMI 22,23 . Motivated by this theory, we used Brillouin light scattering (BLS) to directly measure the predicted asymmetric dispersion shift, which in turn allowed us to determine the magnitude and direction of the DMI vector in a technological relevant sample system: we used a series of sputtered multilayer stacks consisting of SiN/Ni 80 Fe 20 (t)/Pt(6 nm)/Ta(3 nm)/substrate where t ranged from 1 nm to 13 nm.…”
mentioning
confidence: 99%